2007
DOI: 10.1002/jbt.20163
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the toxic effects of Tl+ on isolated rat liver mitochondria in the presence of nonactin

Abstract: The effects of Tl(+) ions on isolated rat liver mitochondria were studied in the presence of nonactin, a cyclic ionophore. Nonenergized rat liver mitochondria were increasingly swollen at an elevated concentration of Tl(+) in the 160 mOsm medium containing 0-150 mM sucrose and 0-75 mM TlNO(3) or 0-50 mM Tl acetate. On the contrary, mitochondria in experiments with nonactin were contracted in the medium with 5-25 mM Tl(+) and were swollen only in the medium with 50-75 mM TlNO(3) or 50 mM Tl acetate. State 4 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 44 publications
(191 reference statements)
4
29
1
Order By: Relevance
“…Nonenergized mitochondria demonstrated massive swelling in the Tl acetate medium [6,7] by Tl + /H + exchange [7]. Further massive swelling of the mitochondria was found after their energization [3,6,7,12]. The swelling is accounted for by electrophoretic uniport of Tl + in the matrix [3,7,11].…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Nonenergized mitochondria demonstrated massive swelling in the Tl acetate medium [6,7] by Tl + /H + exchange [7]. Further massive swelling of the mitochondria was found after their energization [3,6,7,12]. The swelling is accounted for by electrophoretic uniport of Tl + in the matrix [3,7,11].…”
Section: Introductionmentioning
confidence: 93%
“…It was shown that Tl + increased state 4 of rat liver mitochondria [2][3][4][5][6] followed by their uncoupling [3,6,7]. At the same time, no marked effect of Tl + on state 3 and 2,4-dinitrophenol(DNP)-stimulated respiration [2][3][4]6] and on mitochondrial respiratory enzymes [3,[8][9][10] was found. Considering that the inner mitochondrial membrane is easily permeable to Tl + [3,11], nonenergized mitochondria can markedly swell in TlNO 3 medium [6,7,12].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations